Preparation and Characterization of Cellulose-Silica Nanocomposites - Lau, Priscilla Hui Ying (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Environmental concerns of waste paper have led a demanding push to manage the increasing waste paper from daily use. Recycling paper has not been effective in improving the quality of paper. To address this problem, cellulosic waste materials were converted into useful nanocomposite. This provides a very cost-effective way to reduce landfill wastes. NaOH/thiourea/urea solvent was used to dissolve cellulose under suitable conditions as it is environmentally friendly and cheap. Silica sol was prepared using sol-gel method and added to dissolved cellulose to prepare cellulose nanocomposite.The morphology and changes in functional groups were characterized using Scanning Electron Microscope (SEM) and Fourier Transfer Infrared (FTIR) spectroscopy